Endometriosis and oocyte quality: an analysis of 13 614 donor oocyte recipient and autologous IVF cycles. Issue 3 (10th June 2022) - Kamath, Mohan S; Subramanian, Venkatesh; Antonisamy, Belavendra; Sunkara, Sesh Kamal
Abstract: STUDY QUESTION: Does endometriosis affect live birth following donor oocyte recipient versus autologous IVF? SUMMARY ANSWER: There was no significant difference in the live birth rate (LBR) in women with endometriosis undergoing donor oocyte recipient cycles versus autologous IVF cycles. WHAT IS KNOWN ALREADY: For infertile women with endometriosis, IVF is often considered as a treatment option. Lower implantation and pregnancy rates have been observed following IVF in women with endometriosis. It has been debated whether the lower pregnancy rate is due to the effect on oocyte quality or the endometrium, thus affecting implantation. To delineate whether endometriosis affects oocyte quality or the endometrium, we planned a study, using a donor oocyte recipient model, where the recipients were women diagnosed with endometriosis and compared their outcomes with women who underwent autologous IVF, who had also been diagnosed with endometriosis. STUDY DESIGN, SIZE, DURATION: Human Fertilization and Embryology Authority (HFEA) anonymized data from 1996 to 2016 were analyzed. This comprised of a total of 758 donor oocyte recipients, where the recipients were women diagnosed with endometriosis, and 12 856 autologous IVF cycles where the women were diagnosed with endometriosis as the sole cause of infertility. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data on all women with endometriosis undergoing donor oocyte recipient and autologous IVF cycles were analyzed to compare live birth outcomes. Logistic regression analysis was performed adjusting for number of previous IVF cycles, previous live birth, period of treatment, day of embryo transfer, number of embryos transferred and fresh or frozen embryo transfer cycle. MAIN RESULTS AND THE ROLE OF CHANCE: There was no significant difference in the LBR in women with endometriosis undergoing donor oocyte recipient fresh embryo transfer cycles compared to women undergoing autologous IVF fresh embryo transfer cycles (31.6% vs 31.0%; odds ratio (OR) 1.03, 99.5% CI 0.79–1.35). After adjusting for confounders, there was no significant difference in LBR in women with endometriosis undergoing donor oocyte recipient fresh embryo transfer cycles versus autologous fresh embryo transfer cycles (adjusted OR (aOR) 1.05, 99.5% CI 0.79–1.41). There was no significant difference in the LBR in women with endometriosis undergoing donor oocyte recipient frozen embryo transfer cycles compared to women undergoing autologous frozen embryo transfer cycles (19.6% vs 24.0%; OR 0.77, 99.5% CI 0.47–1.25). After adjusting for potential confounders, there was no significant difference in the LBR in women undergoing donor oocyte recipient frozen embryo transfer cycles compared with autologous frozen embryo transfer cycles (aOR 0.85, 99.5% CI 0.51–1.41). LIMITATIONS, REASONS FOR CAUTION: Although the analysis was adjusted for potential confounders, there was no information on the extent and classification of endometriosis as well as oocyte number. Furthermore, adenomyosis is thought to co-exist in women with endometriosis and may have independent pathophysiological mechanisms affecting fertility, for which there was no information. WIDER IMPLICATIONS OF THE FINDINGS: The study shows no difference in LBR between donor oocyte recipient cycles in which all recipients had endometriosis compared to autologous IVF cycles in women with endometriosis. Therefore, this study finding suggests that there may be a minimal or no effect of oocyte quality on IVF outcomes in women with endometriosis. STUDY FUNDING/COMPETING INTEREST(S): No funding was obtained. M.S.K. is an associate editor with Human Reproduction Open . He was not involved in the editorial or peer review process for the manuscript. TRIAL REGISTRATION NUMBER: N/A.